Thoracic spinal cord compression secondary to metastatic synovial sarcoma: case report - Arnold,Paul M. (2009)
Synovial sarcoma is an uncommon malignant soft tissue neoplasm, occurring primarily in adolescents and young adults. It is prevalent in the periarticular soft tissues near large joints of the extremities and rarely involves the trunk. Metastases are not uncommon and usually involve the lungs; metastasis to the thoracic spine is rare. We report the case of a 47-year-old man with a history of synovial sarcoma of the lower back, with subsequent metastases to the lung, penis, and perineum (all previously resected), presenting with a 3-month history of low back pain and lower extremity paresthesias. Magnetic resonance imaging (MRI) demonstrated multiple lesions involving multiple contiguous vertebral bodies, with the mass at T12 compressing the spinal cord. The patient underwent T11-T12 laminectomy, transpedicular decompression, tumor debulking, and posterior fixation and fusion. The patient died six months later due to disease progression. Although not curative, decompression and stabilization of the spine are often necessary in patients who present spinal cord compression.